PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PESERTA PENSIUN PADA PT. TASPEN (PERSERO) CABANG DEPOK - Osta Nababan, Benny; Adra Oktaviani, Tanisa (Economicus, 2018)
This study aims to analyze the factors that affect the satisfaction of participants Pension (Y) at PT.Taspen (Persero) Branch Depok. Independent variables used in this research are Tangible (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Emphaty (X5). The sample of this research is 100 Participants from all population. Data collection techniques in this study using questionnaires and literature study. Data analysis technique using multiple linear regression analysis with SPSS program. The results showed that tangible (X1), reliability (X2), and responsiveness (X3) partially have a significant influence on satisfaction of pension participant (Y) meaning that the better tangible, reliability and responsiveness then the satisfaction of pension participant will increase. Assurance (X4) and Emphaty (X5) are not partially insignificant to the satisfaction of the Pension Participant (Y). The result of calculation of coefficient of determination shows that the satisfaction of the participant of pension is influenced by five independent variables such as tangible (X1), reliability (X2), responsiveness (X3), assurance (X4) and Emphaty (X5) equal to 53,7% and the rest equal to 46, 3% is influenced by other factors.